Spontaneous pseudo-topological silicon quantization for redesigned Si-based Li-ion batteries. (February 2019) - Ogata, Ken; Ko, Dong-Su; Jung, Changhoon; Lee, Jun-Ho; Sul, Soohwan; Kim, Hee-Goo; Seo, Jinah; Jang, Jihyun; Koh, Meiten; Kim, Kihong; Kim, Jin Hae; Jung, In-Sun; et al.
Abstract: Nano-structured silicon anodes are attractive alternatives to graphite in lithium-ion batteries; however, despite recent progress in nano-engineered composites, its use remains limited. One of the issues, particularly in silicon-dominated anodes, is the poor Coulombic efficiency of lithium–silicon processes. Previous studies have shown that repeating the amorphous–crystalline hysteretic lithium–silicon phase transformations can abruptly improve irreversibility and eventually minimize cumulative irreversible lithium consumption in exchange of certain parasitic capacity sacrifice. Here, we reveal mechanism behind the phenomenon that the single phase transformation spontaneously and pseudo-topologically transforms nano-structured silicon into quantum-scale frameworks without gravimetric loss. The way it forms is clearly distinct from ever explored formation mechanism of porous nano-structures such as (electro)chemical etching, Kirkendall voiding, and percolation theory. Further, we implanted the structural transformation feature into lithium-ion full cells, largely redesigning the conventional one, by modulating cathode/anode capacity loading balance and prelithiation dose in the anode to embed the unique feature in the cells. We show that the cell preferentially triggers the efficient irreversibility-depletion phenomenon upon cycling and consequently outperforms conventional silicon-based cells. Graphical abstract: Highlights: Structural transformation of Si anode for Li-ion batteries was studied. The formation mechanism of quantum-scale Si nano-architecture was investigated. TEM coupled with tomography was used to probe the detailed microstructure. The phase-transformation from crystalline Li3.75 Si to amorphous Lix Si induced the formation of nano-pores in Si framework structure.